2013
DOI: 10.2147/dmso.s50209
|View full text |Cite
|
Sign up to set email alerts
|

TRC210258, a novel TGR5 agonist, reduces glycemic and dyslipidemic cardiovascular risk in animal models of diabesity

Abstract: BackgroundPatients with diabesity have a significantly increased risk of developing cardiovascular disease. Therefore, therapy addressing the multiple metabolic abnormalities linked with diabesity and leading to further reduction of cardiovascular risk is highly desirable. Activation of the TGR5 receptor holds therapeutic potential for diabesity. In the present study, we evaluated the efficacy of TRC210258, a novel TGR5 agonist, in clinically relevant animal models of diabesity.MethodsA novel small molecule, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…According to a previous method, CHO‐K1 cells were transiently transfected with human nischarin ( NISCH ), a mouse homologue of the human imidazoline receptor antisera‐selective (IRAS) protein and an expression vector (Origene, Rockville, MD, USA) using the TurboFect transfection reagent (Thermo Fisher Scientific, Pittsburgh, PA, USA). Twenty‐four hours after transfection, cells were incubated with the different concentrations of canavanine (0.01–1 μ mol/L) or agmatine (0.01–1 μ mol/L).…”
Section: Methodsmentioning
confidence: 99%
“…According to a previous method, CHO‐K1 cells were transiently transfected with human nischarin ( NISCH ), a mouse homologue of the human imidazoline receptor antisera‐selective (IRAS) protein and an expression vector (Origene, Rockville, MD, USA) using the TurboFect transfection reagent (Thermo Fisher Scientific, Pittsburgh, PA, USA). Twenty‐four hours after transfection, cells were incubated with the different concentrations of canavanine (0.01–1 μ mol/L) or agmatine (0.01–1 μ mol/L).…”
Section: Methodsmentioning
confidence: 99%
“…One of them has the highest activity in vitro (hTGR5 EC 50 = 0.28 nM, mTGR5 EC 50 = 0.92 nM). Zambad et al (2013) synthesized TRC210258 as a novel TGR5 agonist (Table 1). Zheng et al found small compound WB403 could activate TGR5 and promote GLP-1 secretion (Zheng et al, 2015).…”
Section: The Ligands Of Tgr5mentioning
confidence: 99%
“…According to the previous report [26], CHO-K1 cells were transiently transfected with human nischarin (NISCH) gene, also known as human imidazoline receptor antiseraselective (IRAS) protein, and an expression vector (Origene, Rockville, MD, USA) using the TurboFect transfection reagent (Thermo Fisher Scientific, USA). At 24 h later, the transfected cells were used to treat with allantoin or agmatine at indicated concentrations.…”
Section: Overexpression Of Nisch In Cho-k1 Cellsmentioning
confidence: 99%